Evidence for Sea Water Intrusion in Karstic Aquifer of Karaburun Peninsula, Nw Turkey - Baba, Alper; Gündüz, Orhan; Gündüz, Orhan; Baba, Alper; Şimşek, Celalettin; Elçi, Alper; Murathan, Alim; Sözbilir, Hasan (International Water Association, 2017)
Karstic aquifers are considered to be significant sources of groundwater and are mostly under threat due to sea water intrusion in many parts of the world. Seawater intrusion is also a common problem on karstic aquifers of Karaburun Peninsula in north of Mediterranean Region. The hydrogeology of Karaburun Peninsula is fairly complex and is mostly characterized by highly permeable karstic formations with significant water storage in an otherwise water scarce area. The karstic aquifers of the region were recently found to be under severe salt water intrusion, which significantly altered the position of fresh water/sea water interface as a result of excessive pumping and fault zones controlling the karstic network.
IWA 2nd Regional Symposium on water, wastewater and environment, 22-24 March 2017, Cesme, İzmir
Keywords: Costal aquifer; Groundwater; Karstic aquifer; Seawater intrusion; Karaburun Peninsula